Factors predicting resilience among caregivers of people with chronic illness: A cross-sectional study of Thai caregivers - Kummabutr, Jeeraporn; Buaboon, Natthapat; Keawsriwong, Siriluck (Belitung Nursing Journal, 2025)
Background: Millions of adults in Thailand serve as caregivers, facing significant public health challenges related to caregiver burden and well-being. Resilience is linked to better caregiver outcomes, yet the predictors of resilience are not fully understood. Objective: This study aimed to identify the factors predicting resilience among caregivers of people with chronic illness. Methods: A descriptive, cross-sectional design was used with a sample of 172 caregivers selected through multi-stage random sampling. Data were collected between February 2020 and January 2021 using validated instruments. Data were analyzed using descriptive statistics, bivariate analysis, and multiple regression analysis, with significance set at p <0.05. Results: Caregiver resilience scores were within the normal range (Mean = 61.40, SD = 8.735). In bivariate analysis, 7 out of 10 variables—age, stress, self-efficacy, social support, self-esteem, attitude toward care, and family functioning—were significantly associated with caregiver resilience (p <0.05). Multiple regression analysis revealed that key factors significantly predicting caregiver resilience included self-esteem (β = 0.213, p<0.001), attitude toward care (β = 0.268, p <0.001), family function (β = 0.317, p <0.001), and age (β = -0.114, p = 0.037). In contrast, stress (β = -0.230, p <0.001) and knowledge (β = -0.182, p = 0.001) were negatively related to resilience, indicating that higher stress levels diminish coping abilities and that greater caregiving knowledge may contribute to emotional burden. Together, these predictors explained 56.8% of the variance in caregiver resilience (R² = 0.568), highlighting their substantial influence on caregivers’ ability to manage caregiving challenges. Conclusion: This study identifies key factors that influence caregiver resilience, particularly family support, self-esteem, and attitude toward care, while also highlighting the negative impacts of stress and age on resilience. Nurses play a crucial role in enhancing caregiver resilience by focusing on these factors through family-centered interventions, stress management programs, and psychosocial support. Strengthening these areas can significantly improve the quality of life for both caregivers and patients, leading to more effective caregiving outcomes.